Functional hypothalamic amenorrhea: Impact on bone and neuropsychiatric outcomes - Pedreira, Clarissa Carvalho; Maya, Jacqueline; Misra, Madhusmita (Frontiers in Endocrinology, 2022)
Functional hypothalamic amenorrhea is a state of reversible hypogonadism common in adolescents and young women that can be triggered by energy deficit or emotional stress or a combination of these factors. Energy deficit may be a consequence of (i) reduced caloric intake, as seen in patients with eating disorders, such as anorexia nervosa, or (ii) excessive exercise, when caloric intake is insufficient to meet the needs of energy expenditure. In these conditions of energy deficit, suppression of the hypothalamic secretion of gonadotrophin-releasing hormone (with resulting hypoestrogenism) as well as other changes in hypothalamic-pituitary function may occur as an adaptive response to limited energy availability. Many of these adaptive changes, however, are deleterious to reproductive, skeletal, and neuropsychiatric health. Particularly, normoestrogenemia is critical for normal bone accrual during adolescence, and hypoestrogenemia during this time may lead to deficits in peak bone mass acquisition with longstanding effects on skeletal health. The adolescent years are also a time of neurological changes that impact cognitive function, and anxiety and depression present more frequently during this time. Normal estrogen status is essential for optimal cognitive function (particularly verbal memory and executive function) and may impact emotion and mood. Early recognition of women at high risk of developing hypothalamic amenorrhea and its timely management with a multidisciplinary team are crucial to prevent the severe and long-term effects of this condition.